Effects of fenclorim on rice physiology, gene transcription and pretilachlor detoxification ability - Lifeng Hu; Ying Yao; Ruwen Cai; Lang Pan; Kailin Liu; Lianyang Bai (BMC Plant Biology, 2020)
Abstract Background Fenclorim (Fen) can effectively protect rice from pretilachlor (Pre) injury, but its effects on rice have not been formally evaluated; thus, the Fen mode of action for alleviating the phytotoxicity caused by Pre in rice is not clear. This study aimed to examine the biochemical and physiological effects of Fen on rice and to determine the changes induced by Fen at the transcriptome level. Result The chlorophyll content of rice plants was significantly affected by Pre but not by Fen. The activity of oxidative stress enzymes showed that Fen did not elicit any changes in oxidative stress; however, it reduced lipid peroxidation and oxidative damage induced by Pre. Fen did not affect the uptake of Pre but did affect its persistence in rice. In a transcriptome experiment, Fen upregulated genes in a detoxification pathway. Overall, 25 genes related to detoxification were identified, including P450, GST, and GT. Moreover, qRT-PCR analysis showed that four P450 genes, CYP71Y83, CYP71K14, CYP734A2 and CYP71D55, and two GST genes, GSTU16 and GSTF5, were upregulated by Fen and/or Pre. Conclusion Our work indicates that Fen acts in antioxidative defense in addition to enhancing the metabolism of herbicides in rice.